Bi-institutional retrospective study on the demographics and basic clinical presentation of hidrocystomas. (2nd November 2017) - Maeng, Michelle; Petrakos, Paul; Zhou, Mei; Levine, Benjamin; Lelli, Gary; Setabutr, Pete
ABSTRACT: Hidrocystomas are benign, cystic lesions of eccrine and apocrine sweat glands. The literature on hidrocystomas is sparse, consisting of a handful of case reports and limited retrospective reviews. This is the first known bi‐institutional, retrospective, chart review aimed to elucidate the demographics and basic clinical presentation of hidrocystomas. Medical records of adult patients with a pathological diagnosis of hidrocystoma from September 1, 2008 to August 1, 2015 in the Oculoplastic and Reconstructive Surgery Service at the Illinois Eye and Ear Infirmary (UIC) and Department of Ophthalmology of Weill Cornell Medical College (Cornell) were reviewed. Children under the age of 18 were not included. Data collection included: gender, race, age at diagnosis, laterality, location, total number of lesions, and recurrence. Results from both institutions were compared against each other and as a whole. A total of 107 patients were diagnosed with hidrocystoma on pathology. The mean age of diagnosis was 56 years (22‐85). Hidrocystomas were diagnosed in 69 (64.4%) females and 38 (35.5%) males. Lesions were most commonly found in African American (37.4%), Caucasian (30.8%), and Hispanic (16.8%) patients combined across the two institutions with different patient populations. Lesions were largely unilateral (74.8%) and found on the lower lid (38.6%), lateral canthus (31.2%), upper lid (17.7%), and medial canthus (12.6%). Recurrences were seen in 2.3% of lesions. The majority of recurrences occurred in patients who identified their race as Hispanic (2/5) and Caucasian (3/5). Recurrences were seen in 2 males and 3 females. Apocrine and ecccrine hidrocystomas may be more common in female, African American, Caucasian, and Hispanic patients, presenting most commonly in adults in their mid-fifties. Lesions tend to be unilateral with lower lid lesions being the most prevalent location and medial canthus lesions being the least prevalent location for lesion growth. Recurrences may be most common in Hispanics and Caucasians and less common in African Americans. Although a precise recurrence rate cannot be determined at this time, our data suggests that the recurrence rate is low with current excisional methods.